Toward a reliable detection of arachnophobia: subjective, behavioral, and neurophysiological measures of fear response - Landová, Eva; Rádlová, Silvie; Pidnebesna, Anna; Tomeček, David; Janovcová, Markéta; Peléšková, Šárka; Sedláčková, Kristýna; Štolhoferová, Iveta; Polák, Jakub; Hlinka, Jaroslav; Frynta, Daniel (Frontiers in Psychiatry, 2023)
The administration of questionnaires presents an easy way of obtaining important knowledge about phobic patients. However, it is not well known how these subjective measurements correspond to the patient's objective condition. Our study aimed to compare scores on questionnaires and image evaluation to the objective measurements of the behavioral approach test (BAT) and the neurophysiological effect of spiders extracted from fMRI measurements. The objective was to explore how reliably subjective statements about spiders and physiological and behavioral parameters discriminate between phobics and non-phobics, and what are the best predictors of overall brain activation. Based on a clinical interview, 165 subjects were assigned to either a “phobic” or low-fear “control” group. Finally, 30 arachnophobic and 32 healthy control subjects (with low fear of spiders) participated in this study. They completed several questionnaires (SPQ, SNAQ, DS-R) and underwent a behavioral approach test (BAT) with a live tarantula. Then, they were measured in fMRI while watching blocks of pictures including spiders and snakes. Finally, the respondents rated all the visual stimuli according to perceived fear. We proposed the Spider Fear Index (SFI) as a value characterizing the level of spider fear, computed based on the fMRI measurements. We then treated this variable as the “neurophysiological effect of spiders” and examined its contribution to the respondents’ fear ratings of the stimuli seen during the fMRI using the redundancy analysis (RDA). The results for fear ranks revealed that the SFI, SNAQ, DS-R, and SPQ scores had a significant effect, while BAT and SPQ scores loaded in the same direction of the first multivariate axis. The SFI was strongly correlated with both SPQ and BAT scores. Both SPQ and BAT scores have a high informative value about the subject’s fear of spiders and together with subjective emotional evaluation of picture stimuli can be reliable predictors of spider phobia. These parameters provide easy and non-expensive but reliable measurement wherever more expensive devices such as magnetic resonance are not available. However, SFI still reflects individual variability within the phobic group, identifying individuals with higher brain activation, which may relate to more severe phobic reactions.